Design and Kinematics Simulation of Adhesive Tape Fixing Devices of Self-walking Winding Packaging Robots Based on Adams - Shi Yalei; Wang Liangwen; Liu Yiyang; Li Weiwei; Li Feifei; Li Zipeng (Jixie chuandong, 2023)
Wrap-around packaging is widely used in logistics and transportation packaging. The development of a self-propelled winding and packaging robot can significantly push up the technological progress of the industry, and the key to the development of this robot is the design of the packaging film fixing device. In this study, we propose a packaging film fixing device for a self-propelled wrap-around robot, including a cylinder driven articulated arm, a clamping and turning mechanism, a press tape cutting mechanism, and a tape unfolding mechanism. Based on the mechanism design according to the work requirements, SolidWorks is used to model the structure in three dimensions, and the multi-body kinematic analysis is performed by Adams to verify the feasibility of the mechanism. The simulation results show that the running trajectory of the belt chuck conforms to the planned path and meets the design requirements. The structural design and simulation study in this study provide the basis for the subsequent practicalization of the winding and packaging robot.